Species traits predict assemblage dynamics at ephemeral resource patches created by carrion. - Philip S Barton; Saul A Cunningham; Ben C T Macdonald; Sue McIntyre; David B Lindenmayer; Adrian D Manning (PLoS ONE, 2013)
Carrion is an ephemeral and spatially patchy resource that supports a diverse subset of species linked to nutrient cycling and the decomposition process. A number of studies have separately documented changes in the diversity of plants, arthropods and vertebrates at individual carcasses, but there are few studies that have examined how functional traits of different groups of organisms underpin their responses to carrion patches. We used a carrion addition experiment to compare changes in composition and functional traits of insect and plant assemblages at carcasses compared with control sites. We found that significant changes in insect assemblage evenness and heterogeneity was associated with species' dispersal traits, and that plant assemblage responses to subsequent soil nitrogen changes was most apparent among graminoids and exotic species. Beetles at carcasses were twice as large as their counterparts at control sites during the first week of carrion decomposition, and also had higher wing loadings. Plants with high specific leaf area responded faster to the carcass addition, and twice as many species recolonised the centre of carcasses in exotic-dominated grassland compared with carcasses in native-dominated grassland. These results provide an example of how traits of opportunist species enable them to exploit patchy and dynamic resources. This increases our understanding of how carcasses can drive biodiversity dynamics, and has implications for the way carrion might be managed in ecosystems, such as appropriate consideration of spatial and temporal continuity in carrion resources to promote heterogeneity in nutrient cycling and species diversity within landscapes.